Changes in Biomarkers of Inflammation and Oxidative Status in Dogs Subjected to Celiotomy or Video-Assisted Ovariohysterectomy - Dalmolin, Fabíola; Rubio, Camila Peres; Furlanetto, Carla Sordi; Steffens, Rafael; Hadi, Najla Ibrahim Isa Abdel; da Silva, Adriellen de Lima; Tomazi, Paloma; Antunes, Bernardo Nascimento; Elias, Fabiana; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Brun, Maurício Veloso (MDPI, 2024)
We evaluated the surgical stress response of dogs undergoing three ovariohysterectomy (OVH) techniques. Twenty-nine healthy females were allocated into groups: celiotomy and ligature (CelioSut), celiotomy and bipolar energy (CelioBip), and a video-assisted technique using two portals and bipolar energy (VidBip). Clinical evaluation was performed, and the following blood analyses were determined: acute phase proteins (C-reactive protein and haptoglobin), white blood cell counting (WBC), and biomarkers of oxidative status. The VidBip required more time despite a smaller incision, lower heart rate, and earlier feeding and urination. All groups had high white blood cells counts; the C-reactive protein (CRP) levels peaked at 6 and 12 h in all groups and was higher in the CelioBip and VidBip groups compared to CelioSut; haptoglobin concentrations peaked at 48 h in all groups and increased in dogs of the CelioSut group. Trolox equivalent antioxidant capacity, ferric reducing ability of plasma, cupric reducing antioxidant capacity, and advanced oxidation protein were not significantly different among the groups or time points. Total thiol concentrations were lower in CelioBip and CelioSut groups. All surgical techniques induced an inflammatory and oxidative stress response, but the video-assisted technique produced early clinical recovery. The bipolar device produces fewer disturbances than suspensory ligament rupture and ligature.
Keywords: homeostasis; inflammation; laparoscopy; neutering; oxidative stress